Reconstruction of immigration supervision in realizing national security: orientation and formulation - Gusnud Defani (Journal of Law Science, 2023)
Immigration supervision is a crucial element in maintaining the national security of a country. In the context of globalization and increasing human mobility, Indonesia, as an archipelagic nation with thousands of islands and ports, faces complex challenges related to immigration control. These challenges include the rising number of illegal immigrants, human trafficking, and terrorist threats associated with human mobility. Therefore, this research aims to reconstruct immigration supervision with a focus on achieving national security. The research method used is normative legal research with a legislative approach. This study analyzes relevant regulations in the context of immigration supervision and national security in Indonesia. Data is obtained through document analysis and analyzed qualitatively. The research findings indicate that the current policy orientation of immigration supervision in Indonesia has potential weaknesses such as human rights violations, misalignment with social and economic developments, and a lack of effectiveness in preventing illegal foreign movements. Proposed alternative policy formulations include strengthening international cooperation, developing advanced technology, refining immigration regulations, enhancing immigration officer training, and fostering collaboration among relevant agencies. However, the implementation of these policies also faces several challenges, such as budgetary constraints, inter-agency coordination, human rights protection, international agreements, and continuous education and training. Therefore, strong government commitment, adequate financial support, and a balanced approach to achieving the equilibrium between national security and democratic values and human rights are essential. Thus, Indonesia can continue to advance as a secure and stable nation in the face of evolving global challenges.